PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN BAJA - Riftiasari, Dinar (www.bsi.ac.id, 2016)
The background of this research is many studies on the role of the success of an organization is affected by the job performance, for that every company will try to improve the performance of its employees in achieving organizational goals. The objectives of this research were to identify the effect of motivation and job satisfaction on the employee’s performance. Data analyze used in this research is primer data and using purposive sampling to collect the data, analysis data method in this research is using multylinear regression with SPSS. Respondent in this research are the employee. The result of this research show that indicated that motivation has positive and significant impact in performance; job satisfaction has positive and significant impact on performance; and then jointly motivation and job satisfaction has positive and significant impact on employee’s. Keywords: motivation, job satisfaction, and employee’s performance.